2005
DOI: 10.1515/znc-2005-3-409
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mercury-binding Peptides in Vegetative Parts of Chromolaena odorata

Abstract: Mercury-binding peptides from roots, stems, and leaves of Hg-treated Chromolaena odorata plants were isolated and partially characterized using RP-HPLC and ESI-MS. Upon exposure of C. odorata plants to high concentrations of 1.0 and 2.0 μᴍ Hg(NO3)2 treatments from 0-28 days, they accumulated as much as 125 mg/g (dry wt) Hg in the roots, 15.280 mg/g (dry wt) Hg in the stems, and 0.800 mg/g (dry wt) Hg in the leaves indicating that C. odorata has a high potential as a phytoremediation agent of inorganic mercury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…of the Asteraceae family, commonly known as Siam weed, is abundantly present in different agricultural systems (Roder et al 1995;MacFadyen and Cruttwell 1996). Bioaccumulation pattern and chemistry of the mode and type of accumulation of Hg have already been reported in C. odorata (Velasco-Alinsug et al 2005;Swapna et al 2014). According to Agunbiade and Fawale (2009), Siam weed can be used as biomarker in assessing metal contaminations in the traffic-and solid waste-polluted areas.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…of the Asteraceae family, commonly known as Siam weed, is abundantly present in different agricultural systems (Roder et al 1995;MacFadyen and Cruttwell 1996). Bioaccumulation pattern and chemistry of the mode and type of accumulation of Hg have already been reported in C. odorata (Velasco-Alinsug et al 2005;Swapna et al 2014). According to Agunbiade and Fawale (2009), Siam weed can be used as biomarker in assessing metal contaminations in the traffic-and solid waste-polluted areas.…”
Section: Introductionmentioning
confidence: 78%
“…Owing to the mode of cultivation, i.e. hydroponics which contains all nutrients in optimal conditions inclusive of chelators, absorption and translocation of the elements also get enhanced as opined by several authors (Sinha 1999;Velasco-Alinsug et al 2005;Singh et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…In equimolar LO to metal ratio [2:metal=1:1] As previously reported by others, ESI-MS is a sensitive technique for demonstrating interactions between metal ions and peptides (D'Agostino et al, 1996;Rubino et al, 2004;Velasco-Alinsug et al, 2005;Chekmeneva et al, 2010;Wilken et al, 2010) or amino acids (Burford et al, 2004). In addition, ESI-MS has been used to study metal ion binding to amino acids and small model peptides (Armentrout et al, 2012;Coates et al, 2016;Peckelsen et al, 2017).…”
Section: Dilution Experiments Of 2 With Four Metal Saltsmentioning
confidence: 99%
“…The method of Hernandez et al (1998) as modified by Josue et al (2004) was adopted for the differential centrifugation of the crude subcellular fractions. Previous work showed that the leaves from C. odorata plants had the highest accumulation of Hgbinding biomolecules (Velasco-Alinsug et al, 2005b). A gram of FW tissue samples from the leaves of control and Hg-exposed C. odorata plants were separately homogenized in 20 ml extraction buffer pH 7.5.…”
Section: Differential Centrifugationmentioning
confidence: 99%